Influence Of Onlıne Customer Ratıng, Flash Sale And Hedonıc Shoppıng Motıves To Implus Buyıng On Market Users Place Shoppe - Verry Cyasmoro; Rully Arifiansyah (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This Research used the primary quantitative methods SMART PLS cross sectional survey with sample of 150 responden customer had purchased product through market place shoppe .The selection of respondents customer is was carried out by quantitative techniques, online customer ratings seem to have a positive and significant influence on impulse buying, as indicated by a t-statistic value of 3.573. This suggests that higher online ratings lead to increased impulse buying , there's a significant influence between flash sales and impulse buying, with a t-statistic value of 2.867. This implies that when products are offered in flash sales, there's a notable increase in impulse purchase hedonic shopping motives also show a positive and significant effect on impulse buying, with a t-statistic value of 3.147. This indicates that when people are motivated by pleasure-seeking or experiential factors while shopping, they tend to engage in more impulse buying. Keyword: online customer rating, flash sale, hedonic shoping, impulse buying